The New Paradigm of Italian Disability Regulations, from the Reform Law to the Implementing Decrees, via the New Contracts Code: Change starts with Public Administration (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
This contribution aims to highlight how the realization of a real change in the approach to the protection and inclusion needs of people with disabilities primarily starts with public administrations, to which the legislator seems to have assigned the task of initiating and supporting the paradigm shift necessary to make the principles expressed by the United Nations Convention on the Rights of Persons with Disabilities effective. In this perspective, an analysis of the implementing decrees of the delegated law is proposed, as well as of the system of public bodies resulting from it, also considering those provisions of the recently reformed Public Contracts Code that contribute to the development of increasing inclusion of people with disabilities in the workplace
Keywords: Disability Regulation; Inclusion of Persons with Disabilities; Public Administration and Disability Issues; Public Contracts Code and Social Clauses